Church Denominational Relations in the Perspective of Christian Conflict Management in Paret Village, Kotabunan District, East Bolaang Mongondow Regency - Lumintang, Jimmy Oswal Josua; Selanno, Semuel; Mamahit, Meyke M. (Peneliti.net, 2025)
This study aims to analyze the relationship between church denominations in Paret Village, Kotabunan District, East Bolaang Mongondow Regency, with a focus on the application of Christian conflict management. It also identifies supporting and inhibiting factors in building interdenominational relationships. The study uses a qualitative method with a phenomenological approach, involving observation, interviews, and document analysis. Findings show that relationships between churches in Paret Village are generally harmonious, supported by values of family, cooperation, and shared faith. However, internal tensions remain, especially regarding burial land disputes and denominational exclusivism. The application of Christian conflict management is reflected through dialogue, love in action, and Christ-centered principles. Supporting factors include inter-church activities, spiritual formation, and a culture of peaceful coexistence. Inhibiting factors include denominational fanaticism, weak communication among church leaders, and low participation in joint activities. This study concludes that Christian conflict management plays an essential role in building peaceful and sustainable inter-church relationships